2003
DOI: 10.1111/j.0105-1873.2003.0235.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergenic activity of an air‐oxidized ethoxylated surfactant

Abstract: Ethoxylated surfactants are used in household and industrial cleaners, topical pharmaceuticals, cosmetics and laundry products. Polyethers, e.g. ethoxylated surfactants and polyethylene glycols, are oxidized by atmospheric oxygen (autoxidized) when stored and handled. We have previously shown that a chemically well-defined non-ionic surfactant, the ethoxylated alcohol penta-ethylene glycol mono-n-dodecyl ether (C 12 E 5 ), forms a complex mixture of autoxidation products when exposed to air. Predictive testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The use of cleaning products containing both terpenes and glycol ethers in the presence of O 3 can lead to oxidation of the glycol ethers via OH and perhaps NO 3 (Nazaroff and Weschler 2004); resultant products may include potentially allergenic peroxides and hydroperoxides (Karlberg et al 2003). Modeling indicates that when O 3 and NO 2 are present simultaneously, indoor NO 3 may be the dominant indoor oxidant; NO 3 levels as low as 1 ppt can compete effectively with O 3 and OH in oxidizing various terpenoids (Nazaroff and Weschler 2004).…”
Section: Issuesmentioning
confidence: 99%
“…The use of cleaning products containing both terpenes and glycol ethers in the presence of O 3 can lead to oxidation of the glycol ethers via OH and perhaps NO 3 (Nazaroff and Weschler 2004); resultant products may include potentially allergenic peroxides and hydroperoxides (Karlberg et al 2003). Modeling indicates that when O 3 and NO 2 are present simultaneously, indoor NO 3 may be the dominant indoor oxidant; NO 3 levels as low as 1 ppt can compete effectively with O 3 and OH in oxidizing various terpenoids (Nazaroff and Weschler 2004).…”
Section: Issuesmentioning
confidence: 99%
“…[1,2] In previous experimental studies, [3] we have shown that autoxidation of nonionic alcohol ethoxylates generates products that are skin sensitizers. Specific oxidation products, like hydroperoxides, formaldehyde, ethoxylated aldehydes, and ethoxylated formates, have been identified in autoxidation mixtures of the pure ethoxylated alcohol pentaethylene glycol mono-n-dodecyl ether (C 12 E 5 ; Scheme 1a) used as reference surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…Specific oxidation products, like hydroperoxides, formaldehyde, ethoxylated aldehydes, and ethoxylated formates, have been identified in autoxidation mixtures of the pure ethoxylated alcohol pentaethylene glycol mono-n-dodecyl ether (C 12 E 5 ; Scheme 1a) used as reference surfactant. [3] Two hydroperoxides were identified, namely, 1-hydroperoxy-3,6,9,12,15-pentaoxaheptacosan-1-ol (Scheme 1c) and 16-hydroperoxy-3,6,9,12,15-pentaoxaheptacosan-1-ol (Scheme 1d), the latter being the dominating hydroperoxide in the oxidation mixture. [8] The major oxidation product Keywords: allergens · autoxidation · density functional calculations · ethoxylated surfactants · radicals Abstract: Pathways for formation of previously observed autoxidation products of ethoxylated surfactants have been studied by DFT (B3LYP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both DEP and ragweed enhance ragweed-specifi c IgE, the combination of ragweed and DEP exposure produces a synergistic effect that increases ragweed-specifi c IgE production by 16-fold. [ 33 ] In one study, pure surfactant was found to show no allergenic activity. [ 32 ] Ethoxylated surfactants (ES) are used in household and industrial cleaners, laundry detergents, pharmaceuticals, and cosmetics.…”
Section: Respiratory Sensitization Mixturesmentioning
confidence: 99%